LEARNER CHARACTERISTICS AS PREDICTORS OF ONLINE SOCIAL PRESENCE - Mykota, David; Duncan, Randy (Canadian Journal of Education/Revue canadienne de l’éducation, 2007)
In this study, the authors’ determined the individual learner characteristics of educators enrolled in online courses that influenced social presence (affective social communication). Findings reveal that the number of online courses taken, followed by computer‐mediated communication proficiency, are significant predictors of social presence. Recommendations for the effective use of online learning recognize that instructors must deliberately structure interaction patterns to overcome the potential lack of social presence of the medium. Similarly, quality instructional design and course development strategies need be incorporated with supportive pre‐course instructional activities provided to acquaint novice learners with online learning expectations. Key words: online learning, social presence, learner characteristics, computer‐ mediated communication Cet article porte sur les expériences scolaires de jeunes africano‐canadiens. D’habitude, les chercheurs ont tendance à souligner le piètre rendement scolaire des élèves noirs ou les problèmes reliés à leur échec scolaire ou encore à les présenter de façon stéréotypée comme des personnes bruyantes, paresseuses, portées à commettre des crimes, athlétiques, démunies, dangereuses ou ayant un comportement déviant. Cet article décrit plutôt des élèves noirs albertains qui réussissent bien leurs études en dépit de conditions très difficiles. Les données présentées indiquent que les facteurs comme le milieu familial et les encouragements des parents contribuent au succès scolaire. Mots clés : élèves noirs, succès scolaire, milieu familial, éducation en Alberta